Factors of geography and security in the integration construction: the case of East- Asian integration - A. A. Baykov (Vestnik MGIMO-Universiteta)
The paper analyzes the impact of geography and security threats on the dynamics and forms of integration cooperation in the area of East Asia. In particular, it is concluded that both the institutional features of the integration in Asia Pacific, and approaches in the field of cooperation between local states have been largely predetermined by the system of military cooperation and military-political agreements, which were formed during the "cold war".